(untitled) (Journal of Veterinary Medicine and Animal Production, 2021)
Two groups of local intact black and intact white male goats were included in this study. The two goat groups did not perform exclusively to indicate genetic differences in their non-carcass parameters, but feed intake was significantly greater in the older goats (54.5 vs. 51.5 Kg). The heavier SW and HCW were associated with significantly increased feed intake and gastrointestinal tract contents weights but there was a significantly reduced percent empty gastrointestinal tract in association with the heavier HCW only. Also the percent values for the rumen relative to the gastrointestinal tract were significantly (P<0.05) bigger (20.6 vs. 23.3 % and 20.7 vs. 23.4 %) in the heavier SW and HCW but those of the pluck organs relative to the SW were significantly (P<0.05) smaller (2.61 vs. 2.3 % and 2.57 vs. 2.3 %) in the heavier weights of the SW and HCW contrasts. The animals in these contrast groups also exhibited lower percent values (13.88 vs. 12.63 %, P<0.05 and 13.79 vs. 12.63 %, P<0.05) for TEOC and (41.39 vs 40.39%, P<0.05 and 41.46 vs. 40.32%, P>0.05) for TNEOC, but they cropped more yield (54.45 vs 55.76%,P> 0.05 and 52.99 vs. 56.60%, P<0.001) for TUP. As concerns body maturity effect it was found that the greater body maturity in either respect, SW or EBW, increased significantly feed intake, P<0.01; P<0.05 and gastrointestinal tract contents’ weights P<0.001; P<0.001, percent rumen mean value P<0.05; P>0.05, but inflicted a significant (P<0.001) reduction in the percent, empty gastrointestinal tract 8.82 vs. 7.06%; P<0.01 and 8.79 vs. 7.18%; P<0.01 and the percent TEOC mean values (13.92 vs. 12.20%; and 13.96 vs 12.25%; P< 0.001).